The Critical Role of Going Concern Audit Opinions in Relation to Audit Quality, Firm Size, Growth, and Leverage - Komara, Acep (Jurnal Kajian Akuntansi, 2024)
The importance of going concern audit opinions is critical for various stakeholders in evaluating an organization's financial health and its ability to continue operations in the foreseeable future. This study aims to analyse the influence of audit quality, size, growth and leverage on the going concern audit opinion. This study using quantitative approach, and the purposive sampling method. The population of the study are consumer goods industry for the 2019-2023 period, and 220 observation data are analysed by logistic regression analysis test. The results of this study indicate that company growth, company size and debt equity ratio have no significant effect on going concern audit opinions, while audit quality has a significant effect on going concern audit opinions. The practical implications of this study resonate across auditing, corporate governance, investing, and regulatory practices, signaling a need for heightened awareness and action regarding audit quality and its cascading effects on going concern evaluations.